Intergenerational Developments in Household Saving Behaviour - Mark Vink (New Zealand Government, The Treasury, 2014)
This paper examines the saving behaviour of different generations of households in New Zealand over the period 1984 to 2010 using data from the Household Economic Survey. The paper employs a life-cycle framework to estimate regression models that identify the influence of age and birth year on household saving rates. Consistent with the life-cycle hypothesis, the results show that household saving rates exhibit a hump shape over the life cycle. The results also indicate significant differences in the average saving rates of households from different birth cohorts. From the baby boomers onward, the average saving rates of each generation exceed those of the generation preceding it. Although there are differences between the Household Economic Survey and national accounts saving measures, which present a caveat to the analysis, the paper's findings provide some insight into demographic influences on national household saving trends. The results suggest that the movement of the baby boomers into their higher saving years has contributed positively to aggregate saving rates, but that future effects of population ageing are likely to be negative. On the other hand, it is possible that the lift in saving rates over recent generations will provide an ongoing positive contribution to aggregate saving rates throughout the projection period ending 2030.
Keywords: D14; D91; E21; 330; Household saving; life cycle; age; cohorts; Sparen; Lebensverlauf; Altersgruppe; Kohortenanalyse; Neuseeland